Calcium Regulates Growth and Nutrient Absorption in Poplar Seedlings - Weng, Xiaohang; Li, Hui; Ren, Chengshuai; Zhou, Yongbin; Zhu, Wenxu; Zhang, Songzhu; Liu, Liying (Frontiers in Plant Science, 2022)
As a crucial element for plants, calcium (Ca) is involved in photosynthesis and nutrient absorption, and affects the growth of plants. Poplar is an important economic forest and shelter forest species in China. However, the optimum calcium concentration for its growth is still unclear. Herein, we investigated the growth, biomass, photosynthetic pigment, photosynthetic parameters and products, chlorophyll fluorescence parameters, water use efficiency (iWUE) and antioxidant enzyme activity of “Liao Hu NO.1” poplar (P. simonii × P. euphratica) seedlings at Ca2+ concentrations of 0, 2.5, 5, 10 and 20 mmol·L-1, and studied the absorption, distribution and utilization of nutrient elements (C, N, P, K and Ca) in plants. We found that with increasing calcium gradient, plant height and diameter; root, stem, leaf and total biomasses; net photosynthetic rate (Pn); stomatal conductance (Gs); intercellular carbon dioxide (Ci) level; transpiration rate (Tr); Fv/Fm; Fv/F0; chlorophyll-a; chlorophyll-b; soluble sugar and starch content; superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) levels; and long-term water use efficiency (iWUE) of poplar seedlings increased first and then decreased. These values reached their maximums when the calcium concentrations was 5 mmol·L-1, which was significantly different from the other treatments (P<0.05). Meanwhile, a suitable Ca2+ level promoted the absorption of C, N, P, K and Ca in various organs of poplar seedlings. The absorption of C, N, P and K increased first and then decreased with the increasing calcium concentration, but the optimum calcium concentrations for absorption of different elements in different organs were different, and the calcium concentration in leaves, stems and roots increased gradually. Furthermore, the increase in exogenous calcium content led to a decreasing trend of C/N in different organs of poplar seedlings. C/P and N/P had different results in different organs, and only N/P in leaves showed a significant positive correlation with Ca2+. Conclusively, the results of this study indicate that Ca2+ supply (5 mmol·L-1) is optimal, as it increased growth by enhancing photosynthesis, stress resistance and nutrient absorption.